Personas as Public, Audience, and Stereotype: A Critical Inquiry. - Prochner, Isabel; Godin, Danny (Design Issues)
Personas are a widely used tool in design but have yet to receive much consolidated critical analysis. This article presents a critical inquiry into the creation of personas in design practice and research, culminating in a new way of thinking about persona development. The study employs an integrative literature review of design publications to examine and revisit benefits, potential pitfalls, and accepted wisdom on personas. The article then sets the foundation for a design thinking–based process of persona creation, drawing on persuasive design and participatory design research, and areas for future development of research and inquiry.